Factorise 4x square +4x -15
Answers
Answered by
0
Answer:
consider the factors of the product ac which sum to b
4
x
2
−
4
x
+
1
is in standard form
with
a
=
4
,
b
=
−
4
and
c
=
1
⇒
a
c
=
4
×
1
=
4
and - 2 , - 2 sum to - 4
split the middle term using these factors
4
x
2
−
2
x
−
2
x
+
1
←
factorise in groups
=
2
x
(
2
x
−
1
)
−
1
(
2
x
−
1
)
take out the common factor
(
2
x
−
1
)
=
(
2
x
−
1
)
(
2
x
−
1
)
⇒
4
x
2
−
4
x
+
1
=
(
2
x
−
1
)
2
Step-by-step explanation:
Answered by
0
Answer:
Hiii....
Hope it helps.....
Attachments:
![](https://hi-static.z-dn.net/files/de6/4adef8bc7672b63cc30abe41eff69902.jpg)
nandkishore170876:
ur question is not same as given question
Similar questions